Vibration damping and acoustic characteristics of sisal fibre–reinforced polypropylene composite. (January 2019) - Munde, Yashwant S; Ingle, Ravindra B; Siva, I
Natural fibre composites attract industries because of their low density, low cost and the specific mechanical properties they possess in comparison to synthetic fibres. In this work, the randomly oriented sisal fibre–reinforced polypropylene composites are fabricated using extrusion–injection moulding technique. The aim of this study is to experimentally investigate the effect of fibre weight fraction (0%–30% in step of 10%) on vibrational damping and acoustic characteristics. The impulse hammer excitation technique is used to evaluate the free vibrational characteristics, namely, natural frequency and damping. An impedance tube is used in evaluating the acoustic properties, namely, sound absorption coefficient and transmission loss. Experimental results reveal that increase in fibre loading significantly alter the vibrational and acoustic response of the polypropylene composite. Modal analysis shows that incorporation of sisal fibres by 30 wt.% to polypropylene made the natural frequency superior when compared with other compositions. However, damping becomes worse with higher fibre content. In case of acoustic properties, incorporation of fibres at higher fraction enhances the sound absorption coefficient and transmission loss. Experimental results drive the research in development of such new materials system towards the application of vibration and sound diminutions.